Improving Manggarai's Vocational School Counseling Services with Problem-Solving Learning under Merdeka Curriculum - Marianus Tapung (Green Publisher Indonesia, 2024)
The aim of this study was to enhance the capacity of Guidance and Counseling (BK) services in Manggarai Regency through the Problem Solving Learning Model, targeting BK teachers in vocational education units. To achieve this, BK teachers underwent training focused on various skills including problem identification, problem analysis, solution development, and continuous monitoring. The objective was to equip BK teachers with the necessary tools and techniques to address challenges and provide meaningful guidance to students. The results of the training indicated a high level of enthusiasm among BK teachers in Manggarai Regency. Feedback assessments showed positive ratings, particularly in the areas of problem identification, problem analysis, solution development, and continuous monitoring plans, all of which received an average rating of 3.66, categorizing them as